Optimization in cardiac resynchronization therapy with quadripolar leads offer improvement in cardiac energetics in heart failure patients compared with bipolar leads: HUMVEE Clinical Trial. (25th November 2020) - Antoniou, K; Chrysohoou, C; Dilaveris, P; Konstantinou, K; Manolakou, P; Xydis, P; Magkas, N; Antonakos, V; Kakioris, K; Gatzoulis, K; Skiadas, I; Tousoulis, D
Abstract: Background: Cardiac resynchronization therapy (CRT) is a well-established technique for symptomatic heart failure (HF) patients, producing significant clinical benefits. Recent studies have revealed the potential role of multipoint pacing (MPP) in improving response and clinical outcomes. The aim of this work from the Heart failUre study of Multisite pacing effects on VEntriculoartErial coupling (HUMVEE) trial was to evaluate the association between MPP of the left ventricle vs those of optimized biventricular pacing (optBVP) on: a) ventriculoarterial coupling (VAC) and energy efficiency of the failing heart. Both BVP and MPP mode were optimized according to the optimal VTI value of left ventricular outflow track. Methods: HUMVEE is a single-center, prospective (13 months) trial (clinicaltrials.gov identifier NCT03189368), of 80 NYHA III patients (68±10 years; 75% men; 53% ischemic cardiomyopathy), under optimal tolerated therapy, with standard BVP indication, having being implanted with a CRT system able to deliver both modes of pacing. Echocardiographic measurements, including VAC calculation, 6-min-walking-test and quality of life (MLHF questionnaire) were measured at baseline, 6 months post BVP optimization (right before MPP activation) and at the end of follow-up (6 months post MPP optimization). Cardiac power (CP) was calculated according the equation: CP=Cardiac Output x Mean Aortic Pressure/451. Results: 23 patients (30%), due to inability to deliver MPP, remained in optBVP. Those in MPP had 45% ischemic cardiomyopathy vs. 65% in optBVP patients, (p=0.056); ejection fraction 26.5%, vs. 29.5%, p=0.05; while there was no significant difference in gender, age and baseline NYHA class. Both optBVP and MPP patients improved VAC (baseline: 1, 26±0, 3; CRT: 1.18±0.4; MPP: 1.07±0.06, p=0.07); but only MPP patients significant improved from baseline to 12-months (p=0.02); CP was improved in both groups (p=0.02 in optBVD and p=0.01 in MPP), with MPP patients showing improvement in CP by 30% vs 12% in optBVP (p=0.001); 6-min-walk test was improved in MPP patients by 42% from baseline (p=0.0001), compared to optBVP patients who showed improvement up to 30% (p=0.05) and during the first 6 months only. NtproBNP levels were decreased in all patients (p=0.05 for MPP and p=0.07 for optBVP). Only patients who achieved MPP showed improvement in the Quality of life score (baseline: 31.6±23; optBVD:20.1±17; MPP:15.8±12, p=0.002; while those remained in optBVP showed no significant improvement. Conclusions: MPP is a new, promising biventricular pacing modality offering additive effects on myocardial energy balance, cardiac power, systolic and diastolic ventricular function and aortoventricular coupling. HUMVEE trial illustrates those clinical, imaging and biochemical divergences of MPP from even opt BVP that confer significant improvement in quality of life reflecting better myocardial energy handling in patients with advanced HF and cardiac dysychronization. Funding Acknowledgement: Type of funding source: None